Drivers of globalization of R&D investment by U.S. multinational enterprises: Evidence from industry-level data - Zhou, Yixiao (2016)
Existing country-level and firm-level studies have shed light on the mechanisms driving the globalization of R&D investment by multinational enterprises. However, there is a lack of industry-level evidence on this issue, which is much needed for the robustness of the theoretical and conceptual framework developed from country- and firm-level studies. Therefore, this study examines the determinants of overseas R&D investment by multinational enterprises from a single country, the United States, using an industry-level panel dataset. This study covers U.S. multinational enterprises in seven two-digit-level North American Industry Classification System (NAICS) manufacturing industries in twenty-three countries over the period 1999-2008. The empirical findings suggest that technology-seeking motive, technology-adaptation motive, and access to an abundant pool of researchers exert positive impact on the R&D intensity of U.S.-based multinational enterprises in a host country. The roles of investment position, institutional quality and distance are not found to be robust. These findings are largely consistent with the current theoretical understanding on R&D globalization by multinational enterprises. The findings point to the need for policies that strengthen domestic R&D stock, enhance human capital endowment and support a domestic market that is open to the world in order to attract overseas R&D investment by multinational enterprises.